A lithium slag flotation desulfurization method, a ceramic tile incorporating lithium slag, and a preparation method thereof

CN121044912BActive Publication Date: 2026-10-09JIANGXI HEMEI CERAMICS +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511110264.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2026-10-09
Estimated Expiration
2045-08-08

AI Technical Summary

Technical Problem

[0006]本发明要解决的技术问题在于,针对现有技术的上述缺陷,提供一种锂渣浮选脱硫方法、掺入锂渣的陶瓷砖及其制备方法,旨在解决现有技术中的脱硫技术成本高、脱硫效果不好的问题

Benefits of technology

[0027] The glazed blank is fed into a roller kiln for firing at a temperature of 1050–1150°C for 35–45 minutes to obtain ceramic bricks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121044912B_ABST
    Figure CN121044912B_ABST
Patent Text Reader

Abstract

The application provides a lithium residue flotation desulfurization method, a ceramic tile incorporating lithium residue and a preparation method of the ceramic tile, and comprises the following steps: controlling the particle size of the lithium residue to be treated within a predetermined particle size range, adding water to the lithium residue, and preparing a slurry with a predetermined solid content; adding sodium dodecyl sulfonate and xanthate as a collector to the slurry, and adding sodium silicate as an inhibitor to the slurry, and adjusting the pH of the slurry to a predetermined pH range by using sodium carbonate; stirring the slurry with the adjusted pH to obtain desulfurized lithium residue concentrate, and dehydrating and drying the desulfurized lithium residue concentrate to obtain the flotation lithium residue. Through the complementation of chemical adsorption and physical adsorption, charge regulation and hydrophobic layer strengthening, efficient and selective separation of sulfides is realized, the proportion of the release agent added when the lithium residue is applied to wet ball milling of ceramic blanks is greatly reduced, the slurry performance of the lithium residue blank is significantly improved, the cost is low, and the desulfurization effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic production technology, and in particular to a lithium slag flotation desulfurization method, a ceramic brick incorporating lithium slag, and a method for preparing the same. Background Technology

[0002] The lithium battery industry, as a crucial component of the new energy sector, is developing rapidly, and market demand for lithium batteries is constantly increasing. There are many types of lithium ore, including lepidolite, nepheline, and spodumene. Currently, the main lithium extraction processes include sulfuric acid roasting, sulfate roasting, alkaline roasting, and chlorination roasting. Lithium slag is an industrial waste generated during the sulfuric acid process for producing lithium salts; approximately 8-10 tons of lithium slag are produced for every ton of lithium carbonate produced. In recent years, due to expanding market demand and the rapid development of the lithium salt industry, the output of lithium slag has increased year by year. Lithium slag itself has low value and cannot be effectively utilized, so it can only be stockpiled. This method of disposal not only requires large storage areas but also poses a significant threat to the natural ecosystem and environment. Therefore, how to properly treat and efficiently reuse lithium slag is a critical issue that urgently needs to be addressed.

[0003] Lithium slag is a solid waste generated during the production of lithium salts (such as lithium carbonate and lithium hydroxide), mainly composed of aluminosilicates and residual sulfates (such as CaSO4). As an aluminosilicate, lithium slag contains a large amount of SiO2 and Al2O3, which can be used as a raw material in ceramic body formulations. However, direct use can easily lead to the following problems: poor volume stability; sulfides (such as CaSO4) swell after absorbing water, causing cracking of the body; poor slurry fluidity; sulfide particle agglomeration, reducing the rheological properties of the slurry and seriously affecting the slurry performance during raw material preparation. Therefore, to realize the large-scale application of lithium slag in ceramic bodies, the sulfides must first be treated.

[0004] Existing desulfurization technologies include: (1) chemical neutralization desulfurization, which fixes sulfur by adding alkaline substances, which is not only costly but may also introduce impurities; (2) high-temperature calcination desulfurization, which consumes a lot of energy and does not completely decompose sulfides; (3) water washing desulfurization, which only removes soluble sulfates and is ineffective against insoluble sulfides (such as CaSO).

[0005] Therefore, existing technologies have shortcomings and need to be improved and developed. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a lithium slag flotation desulfurization method, a ceramic brick incorporating lithium slag and its preparation method, in order to address the above-mentioned defects of the prior art, and to solve the problems of high cost and poor desulfurization effect of the existing desulfurization technology.

[0007] The technical solution adopted by this invention to solve the technical problem is as follows:

[0008] The first aspect of this application provides a lithium slag flotation desulfurization method, comprising:

[0009] The particle size of the lithium slag to be treated is controlled within a predetermined particle size range, and water is added to the lithium slag to prepare a slurry with a predetermined solid content.

[0010] Sodium dodecyl sulfonate and xanthate were added to the slurry as collectors, and sodium silicate was added to the slurry as an inhibitor. Sodium carbonate was used to adjust the pH of the slurry to a predetermined pH range.

[0011] The pH-adjusted slurry is stirred to obtain desulfurized lithium slag concentrate, which is then dehydrated and dried to obtain flotation lithium slag.

[0012] In one embodiment of this application, the particle size of the lithium slag to be treated is controlled within a predetermined particle size range, and water is added to the lithium slag to prepare a slurry with a predetermined solid content, comprising:

[0013] The particle size D50 of the lithium slag to be treated is controlled at 14μm to 25μm. Water is added to the lithium slag to prepare a slurry with a solid content of 25% to 35%.

[0014] In one embodiment of this application, the amount of sodium dodecyl sulfonate added is 0.01 to 0.03 wt%; the amount of xanthate added is 0.005 to 0.015 wt%; the amount of sodium silicate added is 0.02 to 0.05 wt%; and the predetermined pH range is 8.5 to 9.5.

[0015] In one embodiment of this application, the pH-adjusted slurry is stirred to obtain desulfurized lithium slag concentrate, comprising:

[0016] The pH-adjusted slurry is stirred using a mechanically agitated flotation machine, with an aeration rate of 0.4–0.6 m³ / s. 3 The flotation rate is 1 / min, and the flotation time is 5-10 minutes to obtain desulfurized lithium slag concentrate; the sulfur content of the desulfurized lithium slag concentrate is ≤3%.

[0017] In one embodiment of this application, the chemical composition of the lithium slag, by mass percentage, includes:

[0018] Loss on ignition: 1.5%–9.5%, SiO2: 40%–60%, Al2O3: 15%–30%, Fe2O3: 1.5%–3.5%, CaO: 5%–15%, MgO: 0.5%–5%, Na2O: 1.5%–8%, K2O: 1.5%–8%, SO3: 7%–15%.

[0019] A second aspect of this application provides a ceramic brick incorporating lithium slag, wherein the raw materials for the ceramic brick, by weight, include:

[0020] The flotation lithium slag prepared by the lithium slag flotation desulfurization method according to any one of claims 1 to 4 consists of 15 to 45 parts, clay 18 to 38 parts, potassium sodium feldspar 40 to 60 parts, mineralizer 2 to 10 parts, and degumming agent 0 to 1.0 parts.

[0021] In one embodiment of this application, the chemical composition of the flotation lithium slag, by mass percentage, includes:

[0022] Loss on ignition: 1.5%–9.5%, SiO2: 40%–60%, Al2O3: 15%–30%, Fe2O3: 1.5%–3.5%, CaO: 5%–15%, MgO: 0.5%–5%, Na2O: 1.5%–8%, K2O: 1.5%–8%, SO3: 1.0%–3.5%.

[0023] In one embodiment of this application, the clay includes one or more of kaolin, bentonite, and mixed mud; the mineralizing agent includes one or more of diopside, black talc, and wollastonite; and the degumming agent includes one or more of a composite diluent, sodium tripolyphosphate, sodium hexadeciphosphate, sodium pentamethasone, sodium humate, and water glass.

[0024] A third aspect of this application provides a method for preparing ceramic bricks based on lithium-doped slag as described above, comprising:

[0025] The raw materials for ceramic tiles are prepared according to the formula, and then wet ball milled to obtain a slurry. The slurry is then spray-dried to obtain powder.

[0026] The powder is pressed into shape to obtain a ceramic green body, and the ceramic green body is then subjected to surface decoration, base glaze application, digital inkjet printing, and top glaze application in sequence to obtain a glazed body.

[0027] The glazed blank is fed into a roller kiln for firing at a temperature of 1050–1150°C for 35–45 minutes to obtain ceramic bricks.

[0028] In one embodiment of this application, the fineness of the mud is controlled to have a residue of 0.5-2.3% on a 325-mesh sieve, and the moisture content of the powder is controlled to be 6.0-8.0 wt%; the water absorption rate of the ceramic brick is less than 0.5%, and the strength of the ceramic brick is greater than 45 MPa.

[0029] The embodiments of this application achieve the following beneficial effects: This application controls the particle size of the lithium slag to be treated within a predetermined particle size range, adds water to the lithium slag to prepare a slurry with a predetermined solid content; sodium dodecyl sulfonate and xanthate are added as collectors to the slurry, and sodium silicate is added as an inhibitor; sodium carbonate is used to adjust the pH of the slurry to a predetermined pH range; the pH-adjusted slurry is stirred to obtain a desulfurized lithium slag concentrate; the desulfurized lithium slag concentrate is dehydrated and dried to obtain flotation lithium slag. This application, by controlling the particle size of the lithium slag to be treated within a predetermined particle size range and using sodium dodecyl sulfonate and xanthate as collectors, and further through complementary chemical and physical adsorption, charge regulation, and hydrophobic layer enhancement, achieves highly efficient and selective separation of sulfides, greatly reducing the proportion of desizing agent added when lithium slag is used in wet ball milling of ceramic blanks, significantly improving the slurry performance of lithium slag blanks, with low cost and good desulfurization effect. Attached Figure Description

[0030] Figure 1 This is a flowchart of a preferred embodiment of a lithium slag flotation desulfurization method according to the present invention.

[0031] Figure 2 This is a diagram of the lithium slag flotation desulfurization process in this invention.

[0032] Figure 3 This is a process diagram of a preferred embodiment of the method for preparing ceramic bricks with lithium slag incorporated in this invention. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of this invention clearer and more explicit, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0034] This invention utilizes flotation desulfurization technology to treat lithium slag, selectively removing sulfides and improving the poor slurry fluidity when used as raw material for ceramic blanks. It addresses the rheological properties of lithium slag slurry in ceramic blanks, establishing a green body formulation system suitable for ceramic production. This promotes the application of lithium tailings in the ceramic industry, gradually making lithium slag production proportional to consumption. This reduces the cost of ceramic green body raw materials, decreases mineral resource consumption, enables more rational utilization of mineral resources, increases the value of lithium slag, reduces its environmental pollution, and achieves green production of ceramic bricks. Furthermore, due to the abundance of fluxing elements in lithium slag, increasing the proportion of lithium slag in the ceramic green body formulation can lower the sintering temperature of ceramic bricks, extending the lifespan of kiln furniture and high-temperature refractory materials, and reducing the production cost of ceramic products.

[0035] The main process route of this application embodiment is as follows: raw material pretreatment—lithium slag flotation—lithium slag dewatering—lithium slag billet preparation—wet ball milling—slurry performance testing—spray drying powdering—pressing and molding—surface decoration—firing. Through composite agent desulfurization process and raw material ratio optimization, efficient removal of sulfides is achieved, improving the slurry properties after wet ball milling of lithium slag billets, reducing firing temperature, and enhancing product mechanical properties.

[0036] The specific problems addressed by this application include:

[0037] First, it addresses the enormous harm that lithium slag causes to the natural ecology and environment, while also enabling the reuse of lithium slag to make more rational use of mineral resources.

[0038] Secondly, it solves the problems of mud rheological properties and degumming difficulties encountered in wet ball milling of lithium slag billets, improves the flow properties of lithium slag billet mud, reduces the addition ratio of degumming agent, and lowers the cost of auxiliary raw materials for billet production.

[0039] Third, address the corrosion of manufacturing equipment and kilns by sulfides.

[0040] Please see Figure 1 , Figure 1 This is a flowchart of the lithium slag flotation desulfurization method in this invention. For example... Figure 1 As shown, the lithium slag flotation desulfurization method described in this embodiment of the invention includes the following steps:

[0041] Step S100: Control the particle size of the lithium slag to be treated within a predetermined particle size range, add water to the lithium slag, and adjust it into a slurry with a predetermined solid content;

[0042] Step S200: Sodium dodecyl sulfonate and xanthate are added to the slurry as collectors, and sodium silicate is added to the slurry as an inhibitor. Sodium carbonate is used to adjust the pH of the slurry to a predetermined pH range.

[0043] Step S300: Stir the pH-adjusted slurry to obtain desulfurized lithium slag concentrate, and dehydrate and dry the desulfurized lithium slag concentrate to obtain flotation lithium slag.

[0044] Specifically, through phase analysis of lithium slag, the sulfides in lithium slag mainly exist in the form of gypsum. Gypsum (CaSO4·2H2O) is a common sulfate mineral in industry and mineral resources, and the key to its flotation separation lies in the selection of flotation agent.

[0045] Xanthates (such as sodium butylxanthate) are typical collectors for sulfide minerals, and their molecular structure contains a thiocarbonyl group (-C=S) and a hydrocarbon chain (hydrophobic group). The mechanism of action of xanthates includes:

[0046] (1) Chemisorption: The sulfur atoms of xanthate react with the metal ions (Fe2, CaS, etc.) on the surface of sulfide minerals. 2+ Ca 2+ (etc.) undergo coordination reactions to form a stable hydrophobic film of metal xanthate.

[0047] (2) Hydrophobicity: Long-chain hydrocarbon groups (such as butyl) extend outward, making the surface of the sulfide hydrophobic and easy for bubbles to adhere and float.

[0048] Sodium dodecyl sulfonate (SDS) is an anionic surfactant with hydrophilic sulfonic acid groups (-SO3). - ) and hydrophobic long-chain alkyl (C 12 H 25 The functions of sodium dodecyl sulfate include:

[0049] (1) Physical adsorption: Sulfonic acid groups are adsorbed on positively charged regions on the surface of sulfides (such as metal cation sites generated by mineral dissociation) through electrostatic interaction, forming a double-layer adsorption structure.

[0050] (2) Wettability regulation: Long-chain alkyl groups cover the mineral surface, further enhancing hydrophobicity, while dispersing fine particles in the slurry and preventing agglomeration.

[0051] In the flotation desulfurization process, xanthate and sodium dodecyl sulfate are used as a combined collector to achieve efficient separation of sulfides through the above-mentioned principles, namely, synergistic effect and selective complementary adsorption. Xanthate has stronger selectivity for lattice sulfur (such as FeS2), but weaker adsorption capacity for partially oxidized sulfur (such as CaSO4); sodium dodecyl sulfate has better adsorption effect on sulfides with surface charge sensitivity (such as calcium and sodium sulfates). The combination of the two can cover different types of sulfides, expanding the desulfurization range. The synergistic effect of xanthate and sodium dodecyl sulfate, through complementary chemical and physical adsorption, charge regulation and hydrophobic layer enhancement, achieves efficient and selective separation of sulfides. The combined reagent system of this application is particularly suitable for treating the removal of multi-form sulfur from lithium slag, laying the foundation for the subsequent high-performance preparation of building ceramic bodies.

[0052] In this embodiment, sodium silicate dissociates in water to generate SiO3. 2- and Na + They preferentially adsorb onto the surface of silicate minerals (such as SiO2 and Al2O3 in lithium slag), forming a hydrophilic layer that inhibits their binding with the collector and reduces the floating of impurities.

[0053] The key role of pH control is that the pulp pH directly affects surface charge and collector activity. In this application, sodium carbonate is used as an alkaline environment (pH 8.5-9.5) adjuster, which can simultaneously inhibit Ca2+. 2+ Concentration, reducing the collector's reaction with free Ca2+ Ineffective consumption due to combination. Under alkaline conditions (pH 8.5–9.5), the negative charge on the sulfide surface is enhanced, and the adsorption of xanthate is affected by electrostatic repulsion. The sulfonic acid group (-SO3) of sodium dodecyl sulfonate... - By compensating for charge, the repulsive force is weakened, and the adsorption of xanthate is promoted.

[0054] This application embodiment controls the particle size of the lithium slag to be treated within a predetermined particle size range and uses sodium dodecyl sulfonate and xanthate as collectors. Through the complementarity of chemical adsorption and physical adsorption, charge regulation and hydrophobic layer enhancement, it achieves efficient and selective separation of sulfides, greatly reduces the proportion of desizing agent added when lithium slag is used in wet ball milling of ceramic billets, significantly improves the slurry performance of lithium slag billets, and has low cost and good desulfurization effect.

[0055] In this embodiment of the application, step S100 specifically involves: controlling the particle size D50 of the lithium slag to be treated to be between 14 μm and 25 μm, adding water to the lithium slag, and adjusting to obtain a slurry with a solid content of 25% to 35%.

[0056] In this embodiment, the raw material pretreatment solid waste is first screened to process the lithium slag particle size D50 to 14μm~25μm, which can make the lithium slag particles more uniform, increase the specific surface area of ​​the particles, and facilitate the adsorption of collectors on the particle surface, thereby improving the flotation efficiency. The slurry with a solid content of 25%~35% has good fluidity and stability, which is conducive to the normal operation of the flotation equipment and the stable progress of the flotation process.

[0057] This application strictly controls the particle size of lithium slag raw materials, keeping the particle size D50 of lithium slag between 14μm and 25μm, so that the reagent can fully react with the sulfides in the lithium slag, thereby improving the desulfurization rate.

[0058] In one embodiment of this application, in step S200, the amount of sodium dodecyl sulfonate added is 0.01 to 0.03 wt%; the amount of xanthate added is 0.005 to 0.015 wt%; the amount of sodium silicate added is 0.02 to 0.05 wt%; and the predetermined pH range is 8.5 to 9.5.

[0059] The collector combination in this application uses sodium dodecyl sulfonate and xanthate to selectively adsorb sulfides. Sodium silicate is then used as a depressant to inhibit the flotation of silicate minerals. The pH is adjusted to 8.5–9.5 to optimize the flotation environment.

[0060] In this embodiment of the application, step S300, "stirring the pH-adjusted slurry to obtain desulfurized lithium slag concentrate," includes: stirring the pH-adjusted slurry using a mechanically agitated flotation machine, wherein the aeration rate of the mechanically agitated flotation machine is 0.4–0.6 m³ / s. 3 The flotation rate is 5-10 minutes, and the flotation time is 5-10 minutes to obtain desulfurized lithium slag concentrate; the sulfur content of the desulfurized lithium slag concentrate is ≤3%.

[0061] In this embodiment, the aeration rate of the mechanically stirred flotation machine is controlled to be 0.4–0.6 m³ / s. 3 The flotation time (5-10 minutes) is adjusted to ensure that sulfides float sufficiently while silicate minerals settle due to their hydrophilicity. The sulfur content of the unfloated lithium slag is 14.78%, and the sulfur content of the desulfurized lithium slag concentrate obtained after desulfurization treatment according to the embodiments of this application is ≤3%.

[0062] Directly using lithium slag in ceramic blanks can lead to a decline in product performance due to sulfide residue, and the H2S generated during calcination can corrode production equipment and pollute the environment. This application addresses the characteristics of sulfides (CaSO4, Na2SO4) in lithium slag by improving sulfide removal rate (up to approximately 80%) through a synergistic "activation-collection" process. In flotation processes, activation refers to improving the surface properties of minerals through chemical or physical means, making them easier to adsorb by flotation reagents, thereby improving floatability and separation efficiency. When the sulfides (CaSO4, Na2SO4) in lithium slag have strong hydrophilicity and are difficult to bind directly to the collector, an activator (such as CuSO4) can be added, whose metal ions (Cu... 2+ The collector reacts with the sulfide surface to form a more hydrophobic metal sulfide composite layer (such as CuS), or changes the surface charge state through ion adsorption, thereby enhancing the collector's adsorption capacity for sulfides. The sulfur content of the desulfurized lithium slag is ≤3.0%, which significantly improves the slurry performance and avoids the problem of product performance degradation due to sulfide residue when lithium slag is directly used in ceramic blanks. It also avoids the problems of H2S generated during calcination causing corrosion to production equipment and environmental pollution.

[0063] In this embodiment of the application, the chemical composition of the lithium slag, by mass percentage, includes:

[0064] Loss on ignition: 1.5%–9.5%, SiO2: 40%–60%, Al2O3: 15%–30%, Fe2O3: 1.5%–3.5%, CaO: 5%–15%, MgO: 0.5%–5%, Na2O: 1.5%–8%, K2O: 1.5%–8%, SO3: 7%–15%.

[0065] Specifically, lithium ores (such as spodumene and lepidolite) are rich in silicates, and unreacted silicon remains as SiO2 after processing; aluminum oxide (Al2O3) comes from aluminosilicate minerals (such as spodumene LiAlSi2O6) in the ore; lime (CaO) may be added during lithium ore processing to neutralize acidic solutions, forming calcium sulfate (CaSO4) or calcium silicate.

[0066] The flotation rate reached approximately 80% using the above composite reagents and optimized flotation process. The chemical composition of the lithium slag before and after flotation, by mass percentage, included:

[0067] Before flotation: Loss on ignition 1.5%–9.5%, SiO2 40%–60%, Al2O3 15%–30%, Fe2O3 1.5%–3.5%, CaO 5%–15%, MgO 0.5%–5%, Na2O 1.5%–8%, K2O 1.5%–8%, SO3 7%–15%.

[0068] After flotation: Loss on ignition 1.5%–9.5%, SiO2 40%–60%, Al2O3 15%–30%, Fe2O3 1.5%–3.5%, CaO 5%–15%, MgO 0.5%–5%, Na2O 1.5%–8%, K2O 1.5%–8%, SO3 1.0%–3.5%.

[0069] Traditional desulfurization methods (such as water washing and high-temperature calcination) suffer from high costs, high energy consumption, low and unstable desulfurization efficiency, and require large amounts of wet grinding desiccant, specifically sodium tripolyphosphate at 1.8%–2.5%. This application's embodiments optimize the flotation reagent combination and process parameters based on the characteristics of sulfides (CaSO4, Na2SO4) in lithium slag, resulting in low cost, high desulfurization rate, and low wet grinding desiccant dosage (sodium tripolyphosphate at 0.5%–0.8%). This significantly improves mud performance, achieving a mud specific gravity of 1.68–1.71 and a flow rate of 35–60 seconds.

[0070] The embodiments of this application improve the sulfide removal rate through the synergistic effect of "activation-collection", so that the sulfide removal rate can reach about 80%. For example, the sulfur content of lithium slag before desulfurization is 11.6%, and the sulfur content of lithium slag after desulfurization is 2.42%. When the proportion of billet is 15% to 45%, the sulfur content is 0.2% to 0.4%.

[0071] The present invention also provides a ceramic brick incorporating lithium slag, wherein the raw materials of the ceramic brick, by weight, comprise:

[0072] The flotation lithium slag prepared by the lithium slag flotation desulfurization method described above consists of 15-45 parts, clay 18-38 parts, potassium sodium feldspar 40-60 parts, mineralizer 2-10 parts, and degumming agent 0-1.0 parts.

[0073] The traditional lithium slag content in ceramic bodies is limited to no more than 10%, making it difficult to achieve the resource utilization of bulk solid waste. The embodiments of this application optimize the flotation process, effectively increasing the lithium slag content to 15% to 45%.

[0074] In this embodiment of the application, the chemical composition of the flotation lithium slag, by mass percentage, includes:

[0075] Loss on ignition: 1.5%–9.5%, SiO2: 40%–60%, Al2O3: 15%–30%, Fe2O3: 1.5%–3.5%, CaO: 5%–15%, MgO: 0.5%–5%, Na2O: 1.5%–8%, K2O: 1.5%–8%, SO3: 1.0%–3.5%.

[0076] In addition to quartz and alumina, the flotation lithium slag in this embodiment contains abundant fluxing agents such as sodium oxide, potassium oxide, calcium oxide, and magnesium oxide, which play a good role in fluxing and mineralization in the green body formulation. During the firing process, the solid-phase reaction temperature for the formation of anorthite is relatively low, at 1000-1050°C, which can significantly reduce the minimum eutectic point of the formulation system and lower the ceramic firing temperature by 80-120°C, thus facilitating low-temperature firing.

[0077] In one embodiment of this application, the clay includes one or more of kaolin, bentonite, and mixed mud; the mineralizing agent includes one or more of diopside, black talc, and wollastonite; and the degumming agent includes one or more of a composite diluent, sodium tripolyphosphate, sodium hexadeciphosphate, sodium pentamethasone, sodium humate, and water glass.

[0078] Mixed clay is a raw material made by mixing and homogenizing kaolin and bentonite to meet the strength, plasticity, whiteness or composition requirements of the billet.

[0079] The clay used in this application mainly comprises kaolin, bentonite, and mixed clay, providing strength to the green body and the finished product. It serves as the basic material for molding, the flux and structural framework for sintering densification, and the main raw material for performance regulation. The mineralizer uses one or a combination of diopside, black talc, and wollastonite, primarily used to adjust the firing profile, firing temperature, product shrinkage, water absorption, and other properties of the green body. The green body degumming agent is used to adjust the slurry properties of the lithium slag green body.

[0080] The present invention also provides a method for preparing ceramic bricks based on lithium-doped slag as described above, wherein the method includes:

[0081] The raw materials for ceramic tiles are prepared according to the formula, and then wet ball milled to obtain a slurry. The slurry is then spray-dried to obtain powder.

[0082] The powder is pressed into shape to obtain a ceramic green body, and the ceramic green body is then subjected to surface decoration, base glaze application, digital inkjet printing, and top glaze application in sequence to obtain a glazed body.

[0083] The glazed blank is fed into a roller kiln for firing at a temperature of 1050–1150°C for 35–45 minutes to obtain ceramic bricks.

[0084] Specifically, by weight percentage, 15-45 parts of flotation lithium slag, 18-38 parts of clay, 40-60 parts of potassium-sodium feldspar, 2-10 parts of mineralizer, and 0-1.0 parts of deflocculant are precisely fed into a ball mill using a belt feeder. After wet ball milling and spray drying, the raw materials are dry-pressed to obtain ceramic green bodies. Surface decoration is then performed, including applying a base glaze after drying and a top glaze after digital inkjet printing. The green body is then fired in a roller kiln at 1050-1150℃ for 35-45 minutes to produce a semi-finished product. The semi-finished products with fully polished surfaces after firing are processed into finished products after rough polishing, fine polishing, edge grinding, air drying, inspection, color separation, and grading. The water absorption rate of the finished products is controlled between 0.1% and 0.5%. The semi-finished products with fine glaze after firing are processed into finished products after edge grinding, air drying, inspection, color separation, and grading. The water absorption rate of the finished products is less than 3.0%.

[0085] The embodiments of this application improve the fluidity, stability and mechanical properties of lithium slag billet slurry, that is, improve the application performance of lithium slag in billet slurry; and adopt a low-temperature fast firing process, with the firing temperature controlled at 1050℃~1150℃ and the firing time at 35min~45min, to achieve low-temperature fast firing.

[0086] In this embodiment of the application, the fineness of the mud is controlled to be 0.5-2.3% residue on a 325-mesh sieve, the moisture content of the powder is controlled to be 6.0-8.0 wt%, the water absorption rate of the ceramic brick is less than 0.5%, and the strength of the ceramic brick is greater than 45 MPa.

[0087] The wet ball milling fineness of the ceramic brick blank slurry in this embodiment is controlled to be 0.5-2.3% residue on a 325-mesh sieve (sieve aperture is 44 micrometers), and the moisture content of the powder is controlled to be 6.0-8.0 wt%; the product water absorption rate is less than 0.5%, and the product strength is greater than 45 MPa.

[0088] The following are specific examples for illustration.

[0089] Example 1:

[0090] The flotation desulfurization process includes the following steps:

[0091] Step A11: Take lithium slag (sulfur content 11.6%) and process it to a particle size D50 controlled at 14μm;

[0092] Step A12: Adjust the slurry to a solid content of 35%, and add compound flotation reagent (collector: 0.02wt% sodium dodecyl sulfonate, 0.005wt% xanthate, inhibitor: 0.03wt% sodium silicate) to adjust the pH to 9.0;

[0093] Step A13, with an inflation volume of 0.6m 3 Flotation was performed at a rate of 5 min for 5 minutes to obtain desulfurized lithium slag (sulfur content 2.42%).

[0094] Step A14: After the above-mentioned composite reagents and optimized flotation process, the flotation rate reached as high as 79.14%. The composition of the lithium slag before and after flotation is as follows:

[0095] Before lithium slag flotation: Loss on ignition 4.2%, SiO2 38.72%, Al2O3 20.12%, Fe2O3 2.56%, CaO 13.94%, MgO 0.73%, Na2O 4.27%, K2O 3.86%, SO3 11.6%;

[0096] After lithium slag flotation: Loss on ignition 2.51%, SiO2 46.08%, Al2O3 24.78%, Fe2O3 2.91%, CaO 12.71%, MgO 0.92%, Na2O 2.06%, K2O 5.61%, SO3 2.42%.

[0097] The production process of ceramic tiles includes the following steps:

[0098] Step A21: Add the flotation lithium slag into the ceramic body formula. The ceramic body formula, by weight percentage, includes: 20 parts flotation lithium slag, 35 parts clay, 40 parts potassium sodium feldspar, 5 parts mineralizer (black talc), and 0.7 parts degumming agent (sodium tripolyphosphate).

[0099] Step A22: Batching. Based on the moisture content of each raw material and the ceramic body formula, a belt feeder is used to accurately transport the batched raw materials to the ball mill.

[0100] Step A23: The raw materials are wet-milled to a slurry fineness of 1.8% (325 mesh sieve residue), a specific gravity of 1.69, and a flow rate of 42 seconds, resulting in good slurry properties;

[0101] Step A24: After the powder is prepared by spray drying, it is dry pressed to obtain a ceramic green body. The moisture content of the powder is controlled at 6.8-7.2 wt%.

[0102] Step A25, surface decoration, which includes applying a base glaze after the ceramic green body has dried, followed by digital inkjet printing and then applying a top glaze;

[0103] Step A26: Firing in a roller kiln using a low-temperature rapid firing process: firing temperature is 1100℃, time is 38 minutes, to produce a semi-finished product;

[0104] The semi-finished products that come out of the kiln are polished, then rough polished, fine polished, edge ground, air-dried, inspected, sorted by color, and graded to obtain finished products. The finished products have a water absorption rate of 0.5% and a flexural strength of 48 MPa.

[0105] Example 2:

[0106] The flotation desulfurization process includes the following steps:

[0107] Step B11: Take lithium slag (sulfur content 12.05%) and process the lithium ore tailings raw material to a particle size D50 controlled at 20μm;

[0108] Step B12: Adjust the slurry to a solids content of 35%, and add compound flotation reagents (collector: 0.03wt% sodium dodecyl sulfonate, 0.01wt% xanthate, inhibitor: 0.03wt% sodium silicate) to adjust the pH to 9.5;

[0109] Step B13, with an inflation volume of 0.6m³ 3 Flotation was performed at a rate of 5 min for 5 minutes to obtain desulfurized lithium slag (sulfur content 2.62%).

[0110] Step B14: After using the above composite reagents and optimized flotation process, a flotation rate of up to 78.26% was obtained. The composition of the lithium slag before and after flotation is as follows:

[0111] Before flotation, the lithium slag composition was as follows: loss on ignition 3.45%, SiO2 45.59%, Al2O3 15.92%, Fe2O3 1.95%, CaO 10.54%, MgO 1.15%, Na2O 5.12%, K2O 4.23%, SO3 12.05%.

[0112] After lithium slag flotation: loss on ignition 2.36%, SiO2 54.08%, Al2O3 18.78%, Fe2O3 2.31%, CaO 10.47%, MgO 1.13%, Na2O 1.69%, K2O 6.56%, SO3 2.62%.

[0113] The production process of ceramic tiles includes the following steps:

[0114] Step B21: Add the flotation lithium slag into the ceramic body formula, which includes: 35 parts flotation lithium slag, 35 parts clay, 28 parts potassium sodium feldspar, 2 parts mineralizer (black talc), and 0.75 parts degumming agent (sodium tripolyphosphate).

[0115] Step B22, Batching: Based on the moisture content of each raw material and the ceramic body formula, use a belt feeder to accurately transport the batched raw materials to the ball mill.

[0116] Step B23: The raw materials are wet-milled to a slurry fineness of 2.0% (325 mesh sieve residue), specific gravity of 1.68, and flow rate of 48 seconds, resulting in good slurry properties.

[0117] Step B24: After the powder is prepared by spray drying, it is dry pressed to obtain a ceramic green body. The moisture content of the powder is controlled at 6.8-7.2 wt%.

[0118] Step B25, surface decoration, which includes applying a base glaze after the ceramic green body has dried, followed by digital inkjet printing and then applying a top glaze;

[0119] Step B26: Firing in a roller kiln using a low-temperature rapid firing process: firing temperature is 1050℃, time is 42 minutes, to produce a semi-finished product;

[0120] The semi-finished products that come out of the kiln are processed into finished products after rough polishing, fine polishing, edge grinding, air drying, inspection, color sorting, and grading. The finished products have a water absorption rate of 0.3% and a flexural strength of 46 MPa.

[0121] Example 3:

[0122] like Figure 2 As shown, collectors and depressants are added to the lithium slag for roughing for 5 minutes, followed by the addition of collectors and depressants for a first scavenging process of 5 minutes; finally, collectors and depressants are added for a second scavenging process of 5 minutes. The final result is lithium slag and sulfur-containing products after flotation.

[0123] Among them, scavenging refers to the next step in processing the roughing tailings when they cannot be discarded as final tailings. The purpose is to improve the metal recovery rate. Sometimes, multiple scavenging processes are required to obtain the final tailings.

[0124] Example 4:

[0125] like Figure 3 As shown, after the ceramic body raw material is crushed and processed, it is batched, and the batched mixture is wet-milled to obtain powder. The powder is pressed into shape, then coated with base glaze, inkjet printing, polished glaze or sprayed with surface glaze, fired, and then ground or polished before being stored.

[0126] This application achieves the following beneficial effects:

[0127] First, this application uses flotation technology for lithium slag desulfurization, achieving efficient and selective separation of sulfur through a specific reagent combination (sulfonate + xanthate + sodium silicate), which greatly reduces the proportion of desizing agent added when lithium slag is used in wet ball milling of ceramic blanks, and significantly improves the slurry performance of lithium slag blanks; it proposes a synergistic formulation of "desulfurized lithium slag-ceramic blanks", breaking through the traditional dosage limit and reducing raw material processing costs.

[0128] Secondly, the synergistic effect of xanthate and sodium dodecyl sulfonate, through complementary chemical and physical adsorption, charge regulation, and hydrophobic layer enhancement, achieves highly efficient and selective separation of sulfides. This combined reagent system is particularly suitable for treating the removal of various forms of sulfur from lithium slag, laying the foundation for the subsequent high-performance preparation of building ceramic blanks. The combined collector can increase the sulfide recovery rate to about 80%, and the sulfur residue in lithium slag ceramic blanks is less than 0.3%, while the sulfur residue in traditional methods is more than 1.0%. Therefore, this application reduces the sulfur residue in ceramic blanks.

[0129] Third, this application incorporates 15% to 45% lithium slag into the ceramic green body. Utilizing the characteristic that lithium slag contains various low-temperature fluxing agents, it can significantly reduce the sintering temperature of the green body, lowering it to 1050℃ to 1150℃. In contrast, the sintering temperature of a green body with a conventional formula is around 1180℃ to 1240℃. Therefore, this application significantly reduces the sintering temperature, and the firing cycle can be controlled within 35 to 50 minutes, realizing a low-temperature rapid firing process for ceramic products, which is beneficial for reducing the manufacturing cost of ceramic products.

[0130] Fourth, this application solves the problem of slag digestion by incorporating a large proportion of lithium slag into the billet, thereby eliminating the huge harm that lithium slag will cause to the natural ecology and environment, and realizing the resource utilization of lithium slag.

[0131] This invention provides a method for desulfurization of lithium slag flotation, ceramic bricks incorporating lithium slag, and their preparation methods. The method includes: controlling the particle size of the lithium slag to be treated within a predetermined particle size range; adding water to the lithium slag to prepare a slurry with a predetermined solid content; adding sodium dodecyl sulfonate and xanthate as collectors to the slurry, and adding sodium silicate as an inhibitor to the slurry; adjusting the pH of the slurry to a predetermined pH range using sodium carbonate; stirring the pH-adjusted slurry to obtain a desulfurized lithium slag concentrate; and dehydrating and drying the desulfurized lithium slag concentrate to obtain flotation lithium slag. This application achieves highly efficient and selective separation of sulfides by controlling the particle size of the lithium slag to be treated within a predetermined particle size range and using sodium dodecyl sulfonate and xanthate as collectors, thereby achieving complementary chemical and physical adsorption, charge regulation, and hydrophobic layer enhancement. This significantly reduces the proportion of desizing agent added when lithium slag is used in the wet ball milling of ceramic blanks, significantly improves the slurry performance of lithium slag blanks, and is low in cost and has a good desulfurization effect.

[0132] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing ceramic bricks based on lithium-doped slag, characterized in that, include: The raw materials for ceramic tiles are prepared according to the formula, and then wet ball milled to obtain a slurry. The slurry is then spray-dried to obtain powder. The powder is pressed into shape to obtain a ceramic green body, and the ceramic green body is then subjected to surface decoration, base glaze application, digital inkjet printing, and top glaze application in sequence to obtain a glazed body. The glazed blank is fed into a roller kiln for firing at a temperature of 1050–1150°C for 35–45 minutes to obtain ceramic bricks. The fineness of the slurry is controlled to have a residue of 0.5-2.3% on a 325-mesh sieve; the moisture content of the powder is controlled to be 6.0-8.0 wt%; the water absorption rate of the ceramic brick is less than 0.5%; and the strength of the ceramic brick is greater than 45 MPa. The raw materials for the ceramic bricks, by weight, include: 15-45 parts of flotation lithium slag prepared by a lithium slag flotation desulfurization method, 18-38 parts of clay, 40-60 parts of potassium-sodium feldspar, 2-10 parts of mineralizer, and 0-1.0 parts of desiccant; the clay includes one or more of kaolin and bentonite; the mineralizer includes one or more of diopside, black talc, and wollastonite; and the desiccant includes one or more of sodium tripolyphosphate, sodium hexapolyphosphate, sodium pentamethasone, sodium humate, and water glass. The lithium slag flotation desulfurization method includes: controlling the particle size of the lithium slag to be treated within a predetermined particle size range; adding water to the lithium slag to prepare a slurry with a predetermined solid content; adding sodium dodecyl sulfonate and xanthate as collectors to the slurry, and adding sodium silicate as an inhibitor to the slurry; adjusting the pH of the slurry to a predetermined pH range using sodium carbonate; stirring the pH-adjusted slurry to obtain a desulfurized lithium slag concentrate; and dewatering and drying the desulfurized lithium slag concentrate to obtain flotation lithium slag. Controlling the particle size of the lithium slag to be treated within a predetermined particle size range, adding water to the lithium slag, and preparing a slurry with a predetermined solid content includes: controlling the particle size D50 of the lithium slag to be treated within 14µm~25µm, adding water to the lithium slag, and preparing a slurry with a solid content of 25%~35%. The amount of sodium dodecyl sulfonate added is 0.01~0.03 wt%; the amount of xanthate added is 0.005~0.015 wt%; the amount of sodium silicate added is 0.02~0.05 wt%; and the predetermined pH range is 8.5~9.

5. The process of agitating the pH-adjusted slurry to obtain desulfurized lithium slag concentrate includes: agitating the pH-adjusted slurry using a mechanically agitated flotation machine, wherein the aeration rate of the mechanically agitated flotation machine is 0.4~0.6 m³ / min, and the flotation time is 5~10 minutes, to obtain desulfurized lithium slag concentrate; the sulfur content of the desulfurized lithium slag concentrate is ≤3%; The chemical composition of the lithium slag, by mass percentage, includes: Loss on ignition 1.5%~9.5%, SiO2 40%-60%, Al2O3 15%-30%, Fe2O3 1.5%~3.5%, CaO 5%-15%, MgO 0.5%~5%, Na2O 1.5%~8%, K2O 1.5%~8%, SO3 7%~15%; The chemical composition of the flotation lithium slag, by mass percentage, includes: loss on ignition 1.5%~9.5%, SiO2 40%~60%, Al2O3 15%~30%, Fe2O3 1.5%~3.5%, CaO 5%~15%, MgO 0.5%~5%, Na2O 1.5%~8%, K2O 1.5%~8%, and SO3 1.0%~3.5%; Xanthate and sodium dodecyl sulfonate work synergistically to achieve efficient and selective separation of sulfides through complementary chemical and physical adsorption, charge regulation, and hydrophobic layer enhancement. At pH 8.5–9.5, the negative charge on the sulfide surface is enhanced, and the adsorption of xanthate is affected by electrostatic repulsion. The sulfonic acid group of sodium dodecyl sulfonate weakens the repulsion force through charge compensation, thus promoting the adsorption of xanthate. By using xanthate to adsorb FeS2 and sodium dodecyl sulfate to adsorb calcium and sodium sulfates, different types of sulfides are covered, thus removing various forms of sulfur from lithium slag. When sulfides in lithium slag cannot directly bind with the collector, an activator is added. The metal ions in the activator react with the sulfide surface to form a more hydrophobic metal sulfide composite layer, or the surface charge state is changed through ion adsorption to enhance the collector's adsorption capacity for sulfides.

Citation Information

Patent Citations

  • Ceramic blank based on lithium slag, ceramic green body, ceramic tile and preparation method of ceramic blank

    CN116715506A

  • Gypsum flotation collector and gypsum flotation method

    CN119076232A